GnRH Antagonist Protocol Versus GnRH Agonist Long Protocol: A Retrospective Cohort Study on Clinical Outcomes and Maternal-Neonatal Safety - Zhu, Jieru; Xing, Weijie; Li, Tao; Lin, Hui; Ou, Jianping (Frontiers in Endocrinology, 2022)
Objective: To evaluate the clinical outcomes and maternal-neonatal safety of gonadotropin releasing hormone antagonist (GnRH-ant) and gonadotropin releasing hormone agonist (GnRH-a) protocols. Methods: A total of 2505 women undergoing their first in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) were retrospectively analyzed. Patients were divided into GnRH-ant group (n = 1514) and GnRH-a group (n = 991) according their stimulation protocol. Propensity Score Matching (PSM) was used for balancing the baseline of two groups. The pregnancy outcomes were analyzed in fresh transfer cycles, and the obstetric and perinatal outcomes were calculated in singleton live births of fresh cycles. The primary outcome was the live birth rate. The secondary outcome measures were maternal complications, preterm birth rate, low birthweight rate, multiple pregnancy rate, and moderate-severe OHSS rate. Results: After 1:1 PSM, baseline characteristics of the GnRH-ant group and GnRH-a group were matched and assigned 991 cycles in each group. Before PSM, there were 700 fresh cycles including 237 singleton live births in the GnRH-ant group and 588 fresh cycles including 187 singleton live births in the GnRH-a group. After PSM, there were 471 fresh cycles including 166 singleton live births in the GnRH-ant group and 588 fresh cycles including 187 singleton live births in the GnRH-a group. No significant differences were observed in the live birth rate (44.6% vs 48.8%), maternal complications, preterm birth rate (9.0% vs 6.4%), and low birthweight rate (17.5% vs 24.1%) between two groups after PSM (P > 0.05). The moderate-severe OHSS rate (2.9% vs 6.0%, P = 0.002) and multiple pregnancy rate (24.5% vs 33.1%, P = 0.025) was significantly lower in the GnRH-ant group than that in the GnRH-a group after PSM. Conclusion: GnRH-ant protocol was comparable with GnRH-a protocol in clinical outcomes, obstetric and perinatal outcomes, and with a lower risk of OHSS. For those who want to get an effective and safe outcome, and a shorter treatment period, GnRH-ant is a suitable choice.